Entrepreneurial growth individual, firm, and region - Corbett, Andrew C.; Katz, Jerome A.; McKelvie, Alexander (Advances in entrepreneurship, firm emergence and growth ;, 2015)
The latest volume of Advances in entrepreneurship, firm emergence and growth examines many questions regarding growth. What decisions and designs of the entrepreneur lead to growth? What are the beginning stages of growth? Are there differences in what drives high growth entrepreneurship versus slower growth entrepreneurship? Are new firms adopting novel approaches to growth? How do growth rates and patterns change over the life of the firm? What policies, infrastructure, and capabilities are necessary to for entrepreneurial regional growth at the macro level? What are the foundational components necessary for growth across all levels of entrepreneurship?